1980
DOI: 10.3382/ps.0592744
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Alfalfa of Varying Saponin Content on Yolk Cholesterol Level and Layer Performance

Abstract: An experiment was carried out for five 28-day periods to determine the effects of feeding rations containing 10% of three alfalfa meals involving varying levels of saponin on the levels of yolk cholesterol and the performance of Single Comb White Leghorn pullets. A corn-soy ration and similar rations with 10% dehydrated alfalfa meal and low (.03%) and high (.62%) saponin suncured alfalfa meal were fed.No significant differences were found in the level of yolk cholesterol, mean hen-day egg production, Haugh uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
3
5
0
1
Order By: Relevance
“…In our study, the LPC used was shown to have no effect on fat and cholesterol contents in egg yolks. These results correspond with those achieved by Nakaue et al (1980), who reported that feeding laying hens with 10% saponin-rich, dehydrated lucerne meal did not alter yolk cholesterol contents. Sim et al (1984) fed laying hens varying levels of a commercial sarsaponin (steroidal saponin)-rich extract from Yucca shottii and also failed to observe any significant effects on egg or serum cholesterol levels; however, they reported that the saponin product decreased feed intake and egg production.…”
Section: Discussionsupporting
confidence: 80%
“…In our study, the LPC used was shown to have no effect on fat and cholesterol contents in egg yolks. These results correspond with those achieved by Nakaue et al (1980), who reported that feeding laying hens with 10% saponin-rich, dehydrated lucerne meal did not alter yolk cholesterol contents. Sim et al (1984) fed laying hens varying levels of a commercial sarsaponin (steroidal saponin)-rich extract from Yucca shottii and also failed to observe any significant effects on egg or serum cholesterol levels; however, they reported that the saponin product decreased feed intake and egg production.…”
Section: Discussionsupporting
confidence: 80%
“…Results obtained in this study confirm the findings that saponin toxicities demonstrated in chicks (Anderson 1957) and in laying hens (Heywang et al 1959) was also counteracted by adding l%o cholesterol to the chick diet (Anderson 1957 This observation confirms reports by other investigators that feeding laying hens either commercial alfalfa meal or alfalfa saponin-extracts did not affect yolk cholesterol levels (Nakaue et al 1980;Weiss and Scott 1979). Early investigations on the inhibitory effect of dietary saponin on chick growth (Peterson 1950) or layer performance (Heywang et al 1959;Anderson 1957) and the counteracting property of dietary cholesterol have provided a base for the hypothesis that dietary saponin forms an unabsorbable cholesterol-saponin complex in the intestinal tract, thereby preventing absorption ofboth exogenous and endogenous cholesterol (Peterson 1950;Cheeke 1913 However, the possibility that a significant portion of taC-radioactivity may be of postabsorptive origin is not eliminated (Sim et al 1980 o (-) duces adsorption of bile salts to dietary fiber and elimination via feces resulting in increased rate of cholesterol metabolism in the liver (Heaton 1972;Oakenfull and Fenwick 1978 It is known that as laying birds progress in maturity, cholesterol biosynthesis increases rapidly due to an increased demand for egg formation (Husbands and Brown 1965) and endogenous origin of cholesterol is more significant than dietary origin in meeting this requirement (Weiss et al 1967;Naber 1983 (Naber 1983).…”
supporting
confidence: 82%
“…However, no significant differences were observed between all other firstorder interactions or among the second-order interactions on the blood parameters of broiler chicks. The decrease in serum cholesterol and triglycerides contents of birds fed the CWC-containing diets may be attributed to cholesterol-binding properties of dietary fibers that may reduce sterol absorption from the gut (Nakaue et al, 1980). The present results agree with those of Abdel-Azeem (2005) who indicated that plasma levels of cholesterol were significantly decreased by increasing dietary crude fiber level.…”
Section: Resultssupporting
confidence: 91%